VILLAGE GOVERNMENT STRATEGY TO REALIZE PARTNERSHIP FOR VILLAGE DEVELOPMENT - Ni Kadek Sinarwati (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE Previous research on partnerships in rural development analyzed the impact of partnership programs. Research on strategies for realizing partnerships is still very limited. This study aims to review the form of partnerships for village development, strategies carried out by village governments, obstacles faced, efforts to overcome obstacles, and supporting factors owned.METHODOLOGY - This research is a qualitative descriptive research. The type of data used was qualitative and quantitative data collected by observation, interview, and documentation methods. The validity of the data is tested by triangulation of method, source, and time.FINDING - The results showed the form of partnerships to develop villages: establishing cooperation with the mother village and neighboring villages, collaborating with universities, providing internet/wifi access, providing officers and village statistical data, and providing data on village SDGs achievement. The strategy taken: proactively coordinating with the parent village, approaching academics, and empowering adolescents as survey officers to record the achievement of Village SDGs. The obstacle faced is the low proportion of tax revenue to the village's gross domestic income. This is overcome by finding new sources of village tax revenue. The supporting factor is the availability of experienced and highly motivated village apparatus to build the village and the strategic location of the village. The research findings have implications for determining policies carried out by village governments in realizing partnerships for village development